PERCEPTION AND ECONOMIC VALUATION OF WAY BELERANG TOURISM IN THE WAY PISANG FOREST MANAGEMENT UNIT (KPH) USING THE TRAVEL COST METHOD - Setiawan, Birgita Diah Puspitrani; Kaskoyo, Hari; Setiawan, Agus; Bakri, Samsul; Wulandari, Christine; Safe'i, Rahmat; Febryano, Indra Gumay (Forestry Study Program University Of Mataram, 2024)
Visitor perceptions and the economic value of tourism greatly influence sustainable tourism development. The aim of the research is to identify visitor perceptions and calculate the economic value of Way Belerang tourism in KPH Way Pisang. Data collection was carried out using interviews, literature studies and documentation. The data that has been collected is then analyzed using a Likert scale, Zonal Travel Cost Method (ZTCM), Individual Travel Cost Method (ITCM) and Multiple Linear Regression. The research results show that the assessment of visitors' perceptions of the facilities is good. Existing facilities are adequate, but repairs need to be made to the ceiling in the rinse area. Promotion and information are not very good because there is not yet complete media available. The tourist attractions are good, the natural attractions and the tourist atmosphere are very supportive. Security and comfort are good, the parking area is large and the guard posts are manned by officers. The average cost to travel to Way Belerang Tourism is IDR 58,876/person/visit, so the economic value of Way Belerang Tourism is IDR 939,725,328/year. Comparison of travel costs based on the visitor's zone of origin within the district Rp. 23,083/zone/visit times, outside the district Rp. 55,195/zone/visit times and outside the province Rp. 114,545/zone/visit times. Supporting promotion and information on Way Belerang requires adequate tools for promoting tourist attractions so that the tourist attractions are more visited by visitors and improving the facilities available at Way Belerang.